Examination of Burnout and State-Trait Anxiety Levels of University Students During the Covid-19 Lockdown in Turkey - Koyuncuoğlu, Özdal (My University, 2022)
In this study, it was aimed to examine university students' higher education burnout and anxiety levels in terms of some variables during the Covid-19 lockdown. In the study, based on correlational and comparative survey method, the burnout and anxiety levels of university students were compared according to the variables of gender, grade level, career expectation, and academic achievement. In addition, the relationship between school burnout and anxiety levels of university students was tried to be explained with the correlational research design. The sample of the study consists of 399 university students studying in Konya and Kırklareli. School Burnout Inventory and State-Trait Anxiety Inventory were used to collect data. According to the research findings, the school burnout of university students during the Covid-19 process was found to be at average values, and their state and trait anxiety were below the average. In addition, university students' school burnout and anxiety levels significantly differed according to gender, grade level, academic achievement, and career expectation variables. Besides, the relationships between school burnout and anxiety levels of university students were found. Ethics committee approval was obtained for the research from the Ethics Committee of Necmettin Erbakan University on 18.06.2021 (No: 2021/361).
Keywords: Turkey; Anxiety; Burnout; Higher Education; Faculty and Vocational High School Students; Demographic Factors